Peran Kepemimpinan Dalam Lembaga Pendidikan Pada Kajian Manajemen Pendidikan Islam - Eneng Siti Suherni; Anis Zohriah; Machdum Bachtiar (Departement of Mathematics Education, 2023)
This study uses a qualitative descriptive method with a literature study approach. Educational institutions certainly need a leader figure, even so what kind of leadership is capable of running an educational institution, does the educational institution need a leader. In general, leadership can be understood as a leader who is able to direct, foster or manage, guide and also show or influence. And educational institutions are a useful container for fostering human beings, leading to a better future. Leadership in educational institutions can be referred to as someone who holds the authority that determines the development of educational institutions. In this paper the author observes that every educational institution known in other words is a school and leadership is someone who is responsible for all progress in the school environment so that in this paper the understanding of leaders and leadership is discussed, leadership urgency, leadership functions, leadership styles and educational leadership in order to make a leader able to manage educational institutions to be better and more advanced